Modelling Learner-Generated Comic Production:An Initial Design - Azman, Farah Nadia; Zaibon, Syamsul Bahrin; Shiratuddin, Norshuhada (Medwell Journals, 2018)
There is an emerging interest in using comics as a digital storytelling medium where learner's knowledge and ideas on various subjects are synthesized in a form of sequential art.However,research that explicitly associates the methods and elements in digital storytelling and educational comic development is scarce. Therefore,this study discusses the concepts,domain and process that leads to the formulation of learner-generated comic production model.The study begins with rationalization of a production model for learner- generated comic.Then,the general approaches for designing and developing the proposed model are elaborated.Finally, the model components are identified and an initial model of learner-generated comic production is proposed.